The red book [large type] - Patterson, James, 1947-; Ellis, David, 1967- (Patterson, James, 1947- Black book thriller, 2021)
Launching an investigation of his own when his instincts tell him that more is behind a political shooting on Chicago's west side, SOS Detective Billy Harney uncovers a spate of murders connected to his troubled past.